The Continued Evolution of the Professional Case Manager Role: A National Study from the Commission for Case Manager Certification. - Tahan, Hussein; Kurland, MaryBeth; Kelley Morgan, Patricia (Professional Case Management)
Purpose: The purpose of this national job-task analysis research study was to identify the roles and functions of professional case managers from the perspective of those currently functioning in such roles, regardless of their professional discipline background. Primary Practice Settings: This study covered the diverse case management practices and/or work settings across the full continuum of health and human services. Methodology and Sample: This cross-sectional descriptive study used the job-task analysis method and online survey research design. It employed a purposive sample of case managers in which an open participation link was e-mailed to more than 68,500 case managers, both certified and not yet certified. A total of 3,297 responses were received, leading to 2,145 as a final acceptable sample for inclusion in the study. Results: Data analysis applied descriptive statistics by survey item, consisting of mean frequency and mean criticality ratings. An importance rating was then computed for each item, applying the multiplicative model that statistically combines the frequency and criticality ratings. The study resulted in an update to the 2019 certified case manager (CCM) test specification blueprint. This included six domains, instead of the previous five, deemed necessary for competent and effective performance by professional case managers. The update was necessary to ensure the certification examination reflects current practice. Implications for Case Management Practice: The study defined how competent and effective professional case management practice has evolved since the 2019 study. It also helps keep the CCM credentialing examination evidence-based and maintains its validity for evaluating the competency of professional case managers. Additionally, the findings are useful for the development of programs and curricula for the training and advancement of case managers.